Construindo o significado do apoio social na adversidade : a experiência da família do doente com câncer em situação de pobreza - Sanchez, Keila de Oliveira Lisboa (2010)
This study aimed to understand the meaning that the family in social vulnerability attributes to the social support and the social network in their experience with cancer. This is a qualitative study guided by Symbolic Interactionism as a theoretical framework, and Grounded Theory as a methodological reference. Data were collected through interviews with families at high social vulnerability, which have one member diagnosed with cancer referred by a Family Health Care Unit in a countryside city in São Paulo. From the continuous comparative analysis of the data emerged two dynamically interrelated phenomena: Realizing themselves vulnerable, which shows the family situation when facing the adversities imposed by the disease and Supporting each other to care, which shows the moves of the family seeking for support to care for the member of the family with cancer while maintaining family balance. Families reorganize and restructure to overcome obstacles and provide care to their beloved, often giving rise to a new family, which includes people who have responded to the demand for social support and exclude those who do not. The social context of these families influences the family system. The interaction that occurs in the subsystems and in the familiar supersystem directly affects the meanings attributed by the families and affect their actions. The relationship of these families with the Public Health System and other Public Services, and especially with the Family Health Care Unit, reveals the difficulties encountered by families to meet their needs. The development of this study offers support to family care of the patient with cancer in a situation of social vulnerability, according to their real needs.